IJCM_397A: A Cross-Sectional Study on Dietary Intake In Relation To Sleep Quality Among Undergraduate Engineering Students - Kumaran K; Sujatha P.; Sravani A; Madhavi B. Devi (Wolters Kluwer Medknow Publications, 2024)
Background: Sleep is an important resting state and essential part of life that could have effect on many aspects of life. Life style factors such as physical activity and consumption of certain foods have effect on quality and quantity of sleep. In this context, there were very few studies done in comparing dietary intake & sleep pattern. So, the present study is planned to be conducted among undergraduate engineering students. Objective: 1. To assess the dietary intake and sleep patterns among undergraduate students. 2. To determine the relationship between dietary intake and sleep quality. Methodology: A Cross-sectional analytical study was done among the undergraduate students of a government engineering college in November 2023. Students (n=200) were randomly selected and data was collected using pre-tested, semi structured questionnaire to assess the dietary intake and Pittsburgh sleep quality index questionnaire (PSQI) to assess sleep quality. Results: The mean age of the study population was 20.2 Â± 1.6 years and 54.5% were female. Sleep quality was fairly good among 58%, good in 29%,fairly bad in 11.5%,and very bad in 1.5%. Participants skipping breakfast, lunch and dinner more than three times a week was reported to be 21%,10%, and 16.5% respectively. Conclusion: The quality and quantity of sleep can be influenced by the eating habits. Specific awareness regarding sleep and food intake should be created among the students, as in the long run NCD s can be prevented and to form a healthy nation.